A scoping review of predictors of speech-language pathology student success. (3rd April 2021) - Johnson, Robyn; Purcell, Alison; Power, Emma; Cumming, Steven
ABSTRACT: Successful completion of their degree is important for both speech-language pathology (SLP) students and their university program. One way of supporting students to achieve the required level of competence would be the early identification of students most in need of additional support. Little is known about predictors of speech-language pathology student success. This paper describes a scoping review aiming to identify the range of factors known to contribute to SLP students' performance in their degree programs. Astin's Input-Environment-Outcome model (1991) was used as a conceptual framework. Four databases were searched, as were references and citations of identified papers. Peer reviewed papers, theses and conference presentations were included. Twenty-one papers and theses from four countries were reviewed. A range of admission criteria and during program factors predict SLP student outcomes during their programs, including discipline understanding, academic skills and test-taking ability. SLP students' discipline knowledge, academic skills and standardized test taking ability can predict their success in their prequalification degree. Identifying students less likely to succeed would allow them to seek support as early as possible and assist educators to provide that support.